2009
DOI: 10.1108/03090560910976410
|View full text |Cite
|
Sign up to set email alerts
|

Shopping orientation and online clothing purchases: the role of gender and purchase situation

Abstract: PurposeThis paper seeks to investigate shopping orientation and online clothing purchases across four different gender‐related purchasing contexts. A conceptual model for understanding the impact of shopping orientation on consumer online clothing purchase is proposed and tested both in a general setting and across purchasing contexts.Design/methodology/approachQuestionnaires were distributed to 1,150 Danish household addresses by use of the “drop‐off‐call‐back” survey method. A total of 441 households returne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
117
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(127 citation statements)
references
References 24 publications
6
117
1
3
Order By: Relevance
“…For retailers in industries such as fashion, the context of this research, this focus on utilitarian motivations is particularly challenging in sectors where online retailers face difficulties recreating the more sensory experience of apparel shopping (Elliott, 2002). Since clothes are an experiential product, the lack of physical contact, uncertainty about product quality or inability to provide the atmosphere experienced in-store have been deterrents to customers purchasing online (Hansen and Jensen, 2009). The adoption of gamification strategies by fashion retailers can therefore be a response to this challenge, and an attempt to build effective customer experiences online as well as offline.…”
Section: Gamification and The Retail Customer Experiencementioning
confidence: 99%
“…For retailers in industries such as fashion, the context of this research, this focus on utilitarian motivations is particularly challenging in sectors where online retailers face difficulties recreating the more sensory experience of apparel shopping (Elliott, 2002). Since clothes are an experiential product, the lack of physical contact, uncertainty about product quality or inability to provide the atmosphere experienced in-store have been deterrents to customers purchasing online (Hansen and Jensen, 2009). The adoption of gamification strategies by fashion retailers can therefore be a response to this challenge, and an attempt to build effective customer experiences online as well as offline.…”
Section: Gamification and The Retail Customer Experiencementioning
confidence: 99%
“…Some previous studies have found that online shopping reduces the costs of information search and makes it is easier to find less expensive items 6,19 . Jensen indicates that consumers are particularly sensitive to price fluctuations during economic recessions 15 .…”
Section: Price Orientationmentioning
confidence: 99%
“…They segment off-line shoppers into fearful conservatives, shopping averters, and technology-muddlers. These orientations are important in relating customer preferences to different shopping channels 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some groups and categories of products and services which are particularly interesting for the users of the Internet, including SM, both in terms of searching for information as well as online shopping. In the group of goods one of the top categories are clothing and shoes as well as broadly defined fashion [Hansen, Jensen 2009]. They are more often more expensive products and buying them requires spending larger sums of money.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%